The Story of Barzu As Told by Two Storytellers from Boysun, Uzbekistan - Rahmoni, Ravshan; van den Berg, Gabrielle (Iranian Studies Series, 2013)
The ancient Persian storytelling tradition has survived until the present day among the Tajik villages in the Gissar mountains of Uzbekistan. This book explores the story of Barzu and demonstrates that the historical Transoxania, since the time of Alexander the Great, has always been a melting pot of diverse shared cultures. In the village of Pasurxi, near Boysun in the Surxandaryo region of contemporary Uzbekistan, a vivid oral tradition exists on the basis of stories from the Persian Book of Kings or Šohnoma (Shahnama), composed more than a thousand years ago by the poet Firdavsi (Ferdowsi). These stories deal with the hero Barzu. The storytellers Jura Kamol and Mullo Ravšan composed two different versions of the story of Barzu in the Tajik as spoken in the Surxandaryo region. They used to tell their stories during evening gatherings in the village.